Application of Islamic Values in Improving The Economy at Senduro Lumajang Market Through Local Wisdom - Afifuddin, Mochammad (Proceedings of Annual Conference for Muslim Scholars, 2024)
Senduro Market, located in Lumajang District, is a bustling hub of economic activity. This research aims to explore how local wisdom and Islamic values shape buying and selling interactions in this market. By employing a qualitative field research approach, including direct observation and participatory observation, the study aims to understand the role of local knowledge in fostering harmony and tolerance among market participants. The findings reveal that local wisdom, such as mutual cooperation and deliberation, combined with Islamic economic values, like honesty, fairness, and respect, play a crucial role in maintaining strong social relations within the market community.